METHODOLOGY OF TEACHING NATURAL SCIENCE TO 6TH GRADE STUDENTS THROUGH INTEGRATED LESSONS - Davronova Yulduz Xolmirzo qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the methodology of teaching natural science to 6th grade students through integrated lessons. The study emphasizes the importance of combining multiple scientific disciplines to enhance students’ understanding, engagement, and practical skills. Integrated lessons allow learners to connect conceptsacross biology, physics, chemistry, and environmental science, promoting critical thinking, problem-solving, and interdisciplinary knowledge. The article discusses strategies for implementing integrated lessons, including project-based learning, collaborative activities, and hands-on experiments, highlighting their pedagogical benefits in developing core competencies and scientific literacy in young learners.